Assessing the Impacts of Pediatric Primary Care Parenting Interventions on EI Referrals Through Linkage With a Public Health Database. (March 2020) - Mendelsohn, Alan L.; Cates, Carolyn Brockmeyer; Huberman, Harris S.; Johnson, Samantha B.; Govind, Prashil; Kincler, Naomi; Rohatgi, Rashi; Weisleder, Adriana; Trogen, Brit; Dreyer, Benard P.
We sought to determine whether pediatric primary care interventions targeting positive parenting among low socioeconomic status mothers resulted in reduced referrals to the New York City Early Intervention Program (NYC-EIP). Participants in Building Blocks (BB) and the Video Interaction Project (VIP) were linked with the NYC-EIP administrative dataset to determine referrals. In all, 139 of 422 study participants (31.4%) meeting inclusion criteria were referred to the NYC-EIP. Although referrals did not differ overall by group (VIP 29.8%; BB 33.8%; control 35.3%), differences were found for mothers with education/literacy of seventh grade or higher (interaction p = .02). In that subgroup, VIP was associated with reduced referrals by age 3 years (22.4%; adjusted odds ratio 0.53; 95% confidence interval [0.29, 0.97]), compared with BB (35.0%) and controls (34.3%), with survival analysis showing reduced cumulative risk ( p = .04). We conclude that VIP resulted in reduced referrals for early intervention evaluation among children of mothers with seventh-grade education or higher.